PERTUMBUHAN IN VIVO BULUH SERBUK SARI DALAM STIGMA GINSENG JAWA (TALINUM TRIANGULARE) PASCA PENYERBUKAN BUATAN: EFEK DONOR SERBUK SARI - Rachman, Erlin; Tihurua, Eka Fatmawati (LIPI Press, 2011)
Talinum triangulare Wild. pollen were germinated in vivo in the stigma with three hand pollination treatments based on pollen donor in order to know its germination rate and if the pollen tube growth rate affected by pollen origin. Flower buds were picked at prior to anthesis time and let them to anthesize in laboratory condition. The three pollination treatments were directly excecuted at full anthesis stage and four different incubation times: 5, 10, 15 and 20 minutes. The experiment was conducted twice with about one month interval between November and December 2008. Signifi cantly different pollen tube growth rate was only showed between stigma pollinated by pollen from neighbor fl owers of same individual and stigma pollinated by pollen from next indidual plant. Highest final pollen germination level and tube growth rate was resulted by hand pollination with pollen from neighbour flowers of the same individual called geitonogamy (54.84% and 9.081 ?m per minute). Second highest was pollination with pollen from the flower itself called autogamy (45.92% and 6.806 ?m per minute). The lowest was hand pollination with pollen from flowers of outside individual called exogamy (39.61% and 3.525 ?m per minute). Stagnated growth of pollen tubes after pollination with outside pollen in exogamy at fi rst minutes of incubation may be related to individual adaptation.